Sistema eletrônico embarcado para monitoramento da energia de soldagem com abordagem instrutiva - Nascimento, Lucas Alves do (2019)
The welder needs manual skills to perform his job. In order to prove his skill and meet the requirements of technical standards, the welder must be tested and approved to accomplish weldments without defects. In this scenario, the travel speed and the heat input are prerequisite and must comply with the range stipulated by the WPS (Welding Procedure Specification). However, maintaining these parameters manually is not a trivial task and any oversight causes damage to production. Therefore, this work presents a dedicated signal monitoring system, referred to here as iWTS 1.0, for manual electric arc welding, in particular the welding process by covered/stick electrode process and GTAW (Gas Tungsten Arc Welding), to assist the welder in the field in the control of heat input by means of real time sending of adjustment instructions (increase or decrease of the travel weld speed or diving distance). This system consists of devices (specific hardware and software) for monitoring data acquisition (current and voltage), inedited instrumentation capable of measuring the manual welding speed, interface for data entry of the WPS and for receiving the information by the welder after processing the data. Moreover, a parallel program developed that generates hard data to avoid a subjective welder assessment of the final system operation. This supervisory is able to record the heat input and travel speed versus the commands of increasing/reducing sent by the system to the welder and returns graphs that make it possible to analyze the performance of the welder. The results show that the proposed system, with feedback every 1 second, is in full operation and suitable for use in the field by the welder to control the heat input. As pointed out in the future technological possibilities of iWTS 1.0, it is possible to use it for social inclusion, focusing on the training of the hearing impaired, by sending light signals and vibracall already implemented. Finally, it is considered that all these objectives are confused with a single objective, which is the implementation of a national, innovative and disruptive technology capable of assisting the welder or apprentice, with or without hearing impairment, in making important decisions and in to avoid, for example, drilling the base material and consequently increasing production costs (waste of material and time of execution).